1984
DOI: 10.1176/appi.psychotherapy.1984.38.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Therapy of Anxiety Disorders: Motivating the Resistant Patient

Abstract: The authors discuss several psychotherapy techniques that mix well and are often indispensable adjuncts in the behavioral therapy of treatment-resistant anxiety-disorder patients. These include psychoeducation, family therapy, psychodynamic interpretations, paradoxical injunctions, and assertiveness training. Multimodal approaches are often indicated with patients who would otherwise not tolerate exposure treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Entretanto, a utilização, eficácia ou efectividade das intervenções familiares de inspiração genericamente comportamental estão também documentadas para situações clínicas tão diversas como perturbações bipolares (Miklowitz & Goldstein, 1990;Rea et al, 2003), depressão major, distimia, perturbações do comportamento alimentar, perturbações relacionadas com o consumo de álcool (Monti et al, 1990;Hanrahan et al, 1984) ou outras drogas, perturbações de ansiedade, demência (Marriott et al, 2000), autismo e outras perturbações globais do desenvolvimento, atraso mental, perturbações da aprendizagem, perturbação de hiperactividade com défice de atenção ou perturbações da conduta (Liberman & Liberman, 2003;Falloon, 2005). Em múltiplas situações de doença mental ou somática (Chalder, Tong & Deary, 2002) a abordagem de problemas em conjunto pode permitir a cada um que se sinta mais integrado na sua matriz familiar (ao mesmo tempo que tenta concretizar os seus próprios objectivos pessoais).…”
Section: Quadrounclassified
“…Entretanto, a utilização, eficácia ou efectividade das intervenções familiares de inspiração genericamente comportamental estão também documentadas para situações clínicas tão diversas como perturbações bipolares (Miklowitz & Goldstein, 1990;Rea et al, 2003), depressão major, distimia, perturbações do comportamento alimentar, perturbações relacionadas com o consumo de álcool (Monti et al, 1990;Hanrahan et al, 1984) ou outras drogas, perturbações de ansiedade, demência (Marriott et al, 2000), autismo e outras perturbações globais do desenvolvimento, atraso mental, perturbações da aprendizagem, perturbação de hiperactividade com défice de atenção ou perturbações da conduta (Liberman & Liberman, 2003;Falloon, 2005). Em múltiplas situações de doença mental ou somática (Chalder, Tong & Deary, 2002) a abordagem de problemas em conjunto pode permitir a cada um que se sinta mais integrado na sua matriz familiar (ao mesmo tempo que tenta concretizar os seus próprios objectivos pessoais).…”
Section: Quadrounclassified
“…Among the clinical literature on defiance-based symptom prescription, there are numerous examples of this category. Typically the authors reported that previous treatments had been unsuccessful and used this to justify the defiance-based approach initiated with the client (e.g., Bepko, 1984; Breit, Im, & Wilner, 1983; Hanrahan, Gitlin, Martin, Leavy, & Frances, 1984). Failed psychotherapy, therapeutic impasses, and resistance are all interpersonal processes that revolve around the actions or inactions of both the client and the therapist (de Shazer, 1984; R.…”
Section: Defiance-based Symptom Prescription and Client Reactance/res...mentioning
confidence: 99%